Effects Of Matrix Swelling On Coal Permeability For Enhance Coalbed Methane (Ecbm) And Co2 Sequestration Assessment Part Ii: Model Formulation And Field Application - Ego Syahrial (Testing Center for Oil and Gas LEMIGAS, 2009)
In part II of this two-part paper series, a field permeability model for enhanced methane recovery and CO2 sequestration, incorporating the findings of the current laboratory tests presented in part I is presented. It has been reported that coal matrix swelling/shrinkage associated with CO2, adsorption/desorption are typically two to five times larger than that found for methane, yet there has been no direct measurements of this effect on permeability of coals to CO2. The feasibility of ECBM/CO2 sequestration technology depends very much on the magnitude of matrix swelling effect on permeability, especially in deep, low permeability coal seam reservoirs. The main objective of this research is to investigate and develop numerical models based on the the effects of coal matrix swelling induced by CO2 adsorption on the permeability of different coals which have been undergoing methane desorption under simulated reservoir conditions in the laboratory.